Cole-Cole analysis of thrombus formation in an extracorporeal blood flow circulation using electrical measurement. (March 2017) - Nguyen Huu, D.; Kikuchi, D.; Maruyama, O.; Sapkota, A.; Takei, M.
Abstract: A Cole-Cole analysis of electrical impedance of blood was performed to explore the possibility of monitoring thrombus formation in extracorporeal blood circulation. Thrombus formation experiments were conducted in both static and flowing conditions by changing the coagulability of the bovine and swine blood. Among the four Cole-Cole parameters which are the relaxation frequency f c, the resistance at zero frequency R 0, the resistance at infinite frequency R ∞, shape factor α, the relaxation frequency f c first increased, reached to the characteristic peak and then decreased during thrombus formation. Other Cole-Cole parameters were either monotonically increasing or decreasing throughout the time without any characteristic point. Additionally, change of pattern followed the same increasing/decreasing pattern for all red blood cells (RBCs) concentrations. Simulations were made on the basis of Hanai's mixture formula to evaluate the results. On the basis of evaluation, the peak time is considered as the time to form the RBCs aggregation. Hence, the monitoring of the relaxation frequency f c is the appropriate strategy form thrombus detection. It provides the possibility of visualizing thrombus formation based on the single tomographic image of relaxation frequency distribution instead of multiple tomographic images of impedance at various frequencies in multifrequency electrical tomography.